Evaluasi pada Aplikasi Belajar Programming Menggunakan System Usability Scale - I Komang Bisma Bendesa Jaya; Ida Ayu Gde Suwiprabayanti Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
In this digital era, using learning applications is an alternative way to master programming. Conventional methods are considered less efficient, so a programming learning application is needed that can be adapted to user needs and provide a satisfactory user experience. Usability is an important factor in determining effectiveness and user comfort level. To meet success, a system or application must meet user expectations and produce a positive user experience. The data collected is primary data of a qualitative nature. To evaluate the system, the system usability scale method is used. The research results show that on average 23 respondents, the system usability scale score is 40 (worst imaginable). This score is still below the average, namely 68, so a redesign is needed to improve the user experience of the system.